File of histopathological evaluation of nervous system diseases (1966) - nr 194/66 - M.Dąmbska, dr hab. (1966)
Histological diagnosis: laesio medullae spinalis in regione cervicali post therapiam. Autopsy examination of 61-year-old patient was performed. Neuropathological evaluation in light microscopy was based on brain paraffin sections stained by Hematoxylin-eosin, Cresyl violet, Heidenhain and Van Gieson's stain.At the cervical level, the medulla surrounded by dura laterally very thickened, hypertrophied with collagen fibers. Numerous old and fresh hemorrhages were observed. Medulla and further parts of the meninges were infiltrated by a profuse purulent infiltrate, which also compresses the medulla itself and even marginally passes into the nerve tissue. At this level, only individual nerve cells were visible. Further cervical and thoracic sections also revealed significant damage and lack of nerve cells. Only the lumbar spinal cord presented no significant changes and moderate cellular damage. No neoplastic lesions were detected. .
Clinical, anatomical and histological diagnosis
Keywords: Encephalopathies & Myelopathies